An Appropriate Model for the Estimation of Consumer Time Expenditure Patterns on the Internet - Russel Cooper (European Commission, Joint Research Centre (JRC), 2013)
IPTS recently acquired a consumer internet clickstream database containing the full set of annual (2011) clickstream records for about 25.000 internet users in the five largest EU economies (UK, Germany, France, Italy and Spain). It contains time spend on each webpage and socio-economic characteristics of the internet users. This study describes a model of consumer Internet time use that is capable of empirical implementation with the clickstream database. There is a natural model of Internet search time that could be developed to fit neatly with the database as it currently exists. The basic structure of such a model has been discussed in detail. The study recommends that IPTS should not rely on any existing model of Internet time expenditures. There does not appear to be a good contender in the literature that would adequately address the requirements of IPTS nor the realities of available data. A purpose-built model needs to be considered.
Keywords: C1; D12; D83; 330; consumer demand; consumer behaviour; internet; time allocation; time expenditure; search time